Digitalisasi Artefak Subak: Transformasi Mekanis Tenggala melalui Animasi Prosedural di Water Museum Mandala Mathika - Gede Agus Prayoga; I Putu Gede Suyoga; Ramanda Dimas Surya Dinata (Besaung : Jurnal Seni Desain dan Budaya, 2026)
The cognitive gap between the younger generation and agricultural heritage in museums is often caused by the static nature of artifacts and the limitations of informational media in explaining complex mechanical logic. This research aims to design a 3D educational animation titled "Tenggala" as a digital interpretation medium for traditional Balinese plow artifacts at the Water Museum Mandala Mathika. Utilizing the User-Centered Design (UCD) method, this design integrates accurate mechanical reconstruction with the philosophical narrative of Tri Hita Karana. The design process focuses on a visual simplification strategy through the Nusantara Stylized approach to reduce the audience's cognitive load. The primary reconstruction focus covers four crucial components: the ergonomically modified Uga (neck yoke), the Camok (muzzle), the Tenggala (main body), and the connecting traction ropes. Evaluation results through data triangulation indicate that the animation is highly valid historically according to subject matter experts and functionally effective according to media experts, with minor notes on motion fluidity. Field trials involving 75 junior high school students showed a procedural understanding retention rate of 81.0% and an increase in affective interest in visiting the museum by 90.6%. These findings prove that the narrative-procedural simulation model in 3D animation successfully transforms static physical artifacts into "living knowledge." This research contributes significantly to the epistemological conservation strategy of Subak culture, while positioning visual communication design as a strategic agent in preserving the collective memory of agricultural societies in the digital age.